Sustained Monopolistic Business Relationships: An Interdisciplinarity Case. - Humphries, Andrew; Wilding, Richard D. (Blackwell Publishing Ltd, 2003)
Business-to-business relationships within sustained monopolies, such as those within UK Defence Procurement, have received scant attention by Management Researchers. This is unusual because under these market circumstances there appear to be few incentives to achieve mutually beneficial outcomes despite their strategic policy importance. This paper argues that an understanding of the monopolistic environment using a Transaction Cost Economics theoretical framework and Supply Chain Management, Relationship Marketing and Transaction Cost Economics concepts provides an innovative, interdisciplinarity approach to solving this problem as well as testing aspects of these disciplines empirically in a novel area. This paper describes the results from a substantial research project to test this hypothesis in the UK Defence Procurement situation. It reveals a number of key dynamics within the sustained monopolistic relationships surveyed and suggests considerable potential for further research.
Keywords: Interdisciplinarity; Supply Chain Management; Relationship Marketing; Transaction Cost Economics; monopoly; Defence Procurement